Educação a Distância Aplicada na Prática: Possibilidades em Biologia - Silveira, Jader Luís da (2020)
Education undergoes modifications that accompany technological innovations, such as Distance Learning, access to virtual libraries, communication of students and teachers through virtual social networks, use of applications, among others in the teaching-learning process. Thus, with a scenario in which information arrives with ever faster speed and with Education and its members being involved in this update, it is necessary to make adaptations in the way of teaching and learning in the face of the information society itself and cyberspace. . The work addresses how information and communication technologies (ICTs) are used in education and how communication is involved in the educational field, whether in person or at a distance.